2018
DOI: 10.1080/1350293x.2018.1463907
|View full text |Cite
|
Sign up to set email alerts
|

Maneuvering suspicions of being a potential pedophile: experiences of male ECEC-workers in Sweden

Abstract: Previous research has described a discourse where men working within Early Childhood Education and Care are viewed as potential pedophiles. The aim of this study is to describe and analyze how men, working in Swedish preschools, position themselves in relation to this pedophile discourse. Twenty-five men were interviewed about their work-experiences and the result shows two dominating positions: (1) giving up or (2) maneuvering the pedophile discourse. The discourse is maneuvered by: avoiding certain tasks, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…According to previous studies in varying cultural contexts (Arendt & Northup, 2015;Mertens et al, 2019;Popović, 2018a;Windzio & Kleimann, 2009), news coverage can negatively affect attitudes toward specific groups. The negative influence of news coverage of CSA on attitudes toward male childcare professionals has been suggested before (Eidevald et al, 2018;Munk et al, 2013). To the best of our knowledge, this is the first time this effect has been studied.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…According to previous studies in varying cultural contexts (Arendt & Northup, 2015;Mertens et al, 2019;Popović, 2018a;Windzio & Kleimann, 2009), news coverage can negatively affect attitudes toward specific groups. The negative influence of news coverage of CSA on attitudes toward male childcare professionals has been suggested before (Eidevald et al, 2018;Munk et al, 2013). To the best of our knowledge, this is the first time this effect has been studied.…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that parents associate male childcare professionals with pedophilia and CSA (Rentzou, 2011; Sak et al, 2019). A link between the attention for CSA in news media and a rise in suspicion toward male childcare workers among parents, especially mothers, has been theorized in research (Eidevald et al, 2018; Munk et al, 2013), but to the best of our knowledge this relation has not yet been studied.…”
Section: News Media and Longitudinal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since gender differences was not significance tested because the male group (n = 16) was too small for meaningful inferences to be made, it would be of interest in future studies to explore this with a larger sample of male participants. Previous studies have also demonstrated that men working in early childhood education and care need to relate to the risk that others will think of them as potential pedophiles (Eidevald, 2016;Eidevald et al, 2018;Heikkilä, 2015). From a gender perspective, men who choose to work in early childhood education and care are breaking traditional norms concerning what men are expected to work with (Heikkilä, 2015;Pruit, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With reference to male ECECs the most salient theme uncovered in the literature pertains to fear of being accused of sexual misconduct due to society’s propensity to view them as a sexual threat (Bhana et al, 2021 ; Eidevald et al, 2018 ; Foster & Newman, 2005 ). Case in point, the supposition that male ECECs constitute a sexual threat is identified within Sargent’s ( 2004 ) study as the single greatest hinderance to increasing male participation.…”
Section: Literature Reviewmentioning
confidence: 99%